Optimal intervention design for tonsillitis transmission via compartmental modeling with stability analysis and control strategies - Mehmet Gümüş; Shewafera Wondimagegnhu Teklu; Aleyna Sezgin (Scientific Reports)
Abstract Tonsillitis represents a significant public health concern, particularly for children and adolescents, leading to substantial socioeconomic costs. To address this, we developed a compartmental mathematical model to investigate the disease’s transmission dynamics and determine optimal intervention strategies. The model’s analysis establishes the conditions for disease persistence and eradication. Using optimal control theory, we assessed the effectiveness of preventative measures as well as treatments for both acute and chronic stages of the infection. Our findings demonstrate that a multi-faceted approach is superior to any single strategy. The most effective and robust reduction in disease prevalence is achieved by an integrated strategy that combines prevention with enhanced treatment protocols. This study offers a quantitative tool for public health officials, providing an evidence-based framework to design and implement more effective policies for controlling tonsillitis.